INCIDENCE OF MYCOBACTERIUM-TUBERCULOSIS AND OTHER MYCOBACTERIA ON PULMONARY INFECTIONS IN ARARAQUARA - SP, 1993 - Leite, CQF; Viana, BHJ; Leite, SRA; Juarez, E. (Soc Brasileira Microbiologia, 1995)
The incidence of tuberculosis and other infections by mycobacteria was analyzed in 559 patients admitted to the Tisiology Section of the Special Health Care Unit of Araraquara (SESA). Mycobacteria were isolated from 78 individuals out of this total. Among these patients, 15 were also HIV positive. The occurrence of isolated species was: M. tuberculosis: 69 patients; M. avium-intracellulare: 5 patients; M. fortuitum: 2 patients; M. chelonae: 1 patient; and M. simiae 1 patient. The latter was for the first time isolated from humans in Brazil. In most cases, non tubercular mycobacteria (NTM) were found in the HIV positive patients.
Keywords: TUBERCULOSIS; MYCOBACTERIA; MYCOBACTERIUM-TUBERCULOSIS